DINAMIKA WACANA PEMEKARAN KECAMATAN MANDAU KABUPATEN BENGKALIS MENJADI DARAH OTONOM - Lovelby Sprindwiva; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT In line with the many divisions in the regions, it turns out that there are still many discourses on the expansion of other regions. One of the many discourses on the expansion of the area is the discourse on the division of Mandau Regency which wants to split itself from Bengkalis Regency. The proposal for the formation of the Mandau Regency itself had actually begun in 1999, which was outlined in the DPR-RI Initiative Draft Law (RUU) for the 1999-2004 period and the 2004-2009 period. The purpose of this research is to explain the dynamics of the Discourse on the Expansion of the Mandau District into an Autonomous Region. The research approach used in this study is a qualitative approach. A qualitative approach is research that is used to investigate, discover, describe, and explain the qualities or features of social influence that can be explained, measured or described through a quantitative approach. While the type used in this research is descriptive. Descriptive method is a research method that describes the characteristics of the population or phenomenon being studied. So that this one research method is the main focus is to explain the object of research. So that answers what events or what phenomena occur. The results of this study indicate that as referred to in Article 33 Paragraph (1) of Law no. 23 of 2014, must comply with 2 (two) requirements, namely basic requirements (regional and regional capacity) and administrative requirements. There are several requirements that have not been met in Mandau District such as the Mandau sub-district has not yet fulfilled the area coverage, the economic aspect where the Bengkalis district still really needs the Mandau sub-district to support local government programs to build other sub-districts in Bengkalis district, From socio-cultural aspects such as identity There are fears of the disappearance of Malayism and the spread of certain religions, the administration of the sub-district administration carried out in Mandau sub-district has not gone as expected, and there is no approval from the provincial DPRD and the governor from the provincial area. As well as there are several reasons why the division of Mandau District has not been realized such as being constrained by the moratorium, Different Inter-Elite Visions¸ and weak political elite relations. Keywords: dynamics, discourse, expansion, regional autonomy